UNDERSTANDING CONCEPT AS LEARNING RESULTS AFTER COOPERATIVE LEARNING MODELS (THINK PAIR SHARE) ASSISTANCE LKS ON STUDENT PROGRAM STUDY EDUCATIONAL CHEMISTY UNIVERSITAS PALANGKA RAYA SEMESTER 2TEACHER OF TEACHING 2016/2017 - Sri Wahyutami; Sri Undari Ningsih (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2017)
The purpose of this study is to describe the understanding of the concept of molecular form in the students of class X IPA SMA Negeri 4 Palangka Raya academic year 2016/2017 after learning using the model of TPS (Think Pair Share). This research involves students of class X IPA 2 SMA Negeri 4 Palangka Raya academic year 2016/2017 as many as 25 people. The students' concept comprehension data is obtained by giving essay written test to students before and after learning using TPS model. Data were analyzed descriptively to explain the change of understanding of student concept as learning result. The results showed that students' understanding of molecular material before learning using TPS was 51% and after learning was 84.1%. The students' success in understanding the concept of molecular form of each learning objective is that students are able to write the electron configuration of 79.2%, the students are able to determine the valence electron of 79.2%, the students are able to illustrate the Lewis symbol of each atom of 80.8% 100% of atomic atoms, students able to describe Lewis structure of compound equal to 85.6%, students are able to determine the number of Free Electron Pairs (PEB) and Electron Pairs of Bonds (PEI) of 92.4%, and students are able to describe molecular shape of 42, 8%